First report of Rickettsia raoultii in field collected Dermacentor reticulatus ticks from Austria - Duscher, Georg G; Hodžić, Adnan; Weiler, Martin; Vaux, Alexander G C; Rudolf, Ivo; Sixl, Wolfdieter; Medlock, Jolyon M; Versteirt, Veerle; Hubálek, Zdenek (Ticks and tick-borne diseases, 2016)
In a set of pooled field collected Dermacentor reticulatus ticks, Rickettsia raoultii, the causative agent of Tick-borne lymphadenopathy/Dermacentor-borne necrosis erythema and lymphadenopathy, was found for the first time in Austria. The coordinates of the positive locations for tick and pathogen abundance are given and shown in a map.
Keywords: Animals; Dermacentor; Rakousko; Austria; zvířata; Rickettsia